(untitled) (Botanica Orientalis: Journal of Plant Science, 2019)
Parthenium hysterophorus is a highly invasive weed in tropical and subtropical regions of the introduced range, and one of the mechanisms suggested to explain the invasion success is allelopathic interference with co-occurring species in invaded habitats. In this study, we examined impacts of aqueous extracts (5%, w/v) of leaf and infloresence of P. hysterophorus on seed germination of 19 herbaceous plant species of Nepal, representing both native as well as alien species. Seeds of test species were collected from roadside vegetation and fallow lands of four urban areas in central Nepal where P. hysterophorus is invading. Germination response of test species to aqueous extracts of P. hysterophorus varied significantly across the species; it ranged from complete suppression (Dactyloctenium aegyptium) to slight enhancement (Senna occidentalis). Out of 19 test species, four were sensitive, three moderately sensitive, and ten resistant with relative germination <33%, 33–66% and >66% in extracts, respectively. Leaf extract of P. hysterophorus has slightly higher inhibitory effect (low germination of test species) than inflorescence extract. Native species appeared to be more sensitive to germination suppression by extracts than aliens. Our results suggest that allelopathic interference of P. hysterophorus with native species can be one of the mechanisms for invasion success of this weed in the introduced range.